Strengthening effect of steel plates on seismic behaviors of RC shear walls with various size post-openings. (May 2023) - Li, Gongchan; Liu, Meng; Pan, Zheren; Lu, Limin; Yuan, Guanglin
Abstract: Quasi-static tests were carried out on the RC shear walls with various size post-openings, 550 mm × 650 mm (12%), 700 mm × 850 mm (20%) and 850 mm × 1000 mm (28%), the strengthening effects of steel plates on the bearing capacity, ductility, energy dissipation capacity and shear deformation of shear walls with different opening sizes were analyzed. The results show that pasting steel plates around the openings can effectively restrain the crack at the corner of the opening and improve the integrity of the shear wall. The bearing capacity of the strengthened shear wall is significantly improved, and accelerates by the increase of opening size. The failure mode of shear walls with various size post-openings changed from wall limb shear failure to "limb hinge" failure, and the failure mode of the strengthened specimens is extremities compressive failure. the ductility of the specimens increases with the increase of the opening rate until it reaches the inflection point. The shear wall with a large opening rate tends to behave like a frame structure, the wall limbs experienced large angular deformation, and pasting steel plates has a negative effect on its ductility.